Distribution of bacteriocin genes in the lineages of Lactiplantibacillus plantarum - Sungmi Choi (Nature Portfolio, 2021)
Abstract Lactiplantibacillus plantarum, previously named “Lactobacillus plantarum,” is found in a wide variety of environments exhibiting a high level of intraspecies genetic diversity. To investigate the strain diversity, we performed comparative genomic analyses of the 54 complete genome sequences. The results revealed that L. plantarum subsp. plantarum was split into three lineages, A, B and C. Of the genes beneficial for probiotic activity, only those associated with the biosynthesis of plantaricin (Pln), an L. plantarum-specific bacteriocin, were found to be significantly different among the lineages. The genes related to the biosynthesis of plnE/F were conserved throughout the three lineages, whereas the outgroups did not possess any Pln-producing genes. In lineage C, the deepest and ancestral type branch, plnE/F genes, were well conserved. In lineage B, loss of gene function was observed due to mobile elements in the pln loci. In lineage A, most strains were predicted to produce more than one type of Pln by possessing diverse Pln-encoding genes. These results showed the presence of functional diversity arising from the trifurcating evolution in L. plantarum subsp. plantarum and demonstrated that Pln is an indicator for differentiating the three lineages.